Protocol and clinical characteristics of patients under ‘at-home care’ for COVID-19 in South Korea: a retrospective cohort study - Jin Ju Park; Yu Bin Seo; Jacob Lee; Sun Hee Na; Young Kyun Choi (BMJ Open)
Objective As the number of patients with COVID-19 increased, at-home care was introduced for the first time in South Korea. This study aimed to analyse the characteristics and outcomes of patients who were treated under at-home care.Design, setting and participants This retrospective cohort study targeted patients under at-home care for COVID-19 in Yeongdeungpo-gu in Seoul, Korea, from 18 October 2021 to 12 December 2021. The public health centre selected eligible patients for at-home care and registered with our institution. Nurses monitored patients, and doctors decided to transfer healthcare facilities and release the quarantined patients according to their symptoms.Outcome measures Patient characteristics during the course of at-home care.Results A total of 1422 patients were enrolled and 9574 patient-days were managed. Most patients were aged ≥60 years (22.7% (n=323)), and 82.8% did not have underlying conditions. The median length of care for patients was 8 days (IQR: 5–10 days). During the study period, 986 (69.3%) patients were released from quarantine, 82 (5.8%) patients were transferred to facilities and 354 (24.9%) patients were still under at-home care at the end of the study period. The most common cause of transfer was sustained fever (n=30; 36.6%), followed by dyspnoea and desaturation (n=17; 20.7%). Factors associated with transfer were diabetes (OR: 3.591, 95% CI 1.488 to 8.665, p=0.004), pregnancy (OR: 5.839, 95% CI 1.035 to 32.935, p=0.046) and being presymptomatic at diagnosis (OR: 4.015, 95% CI 1.559 to 10.337, p=0.004).Conclusions There were no specific problems related to patient safety when operating at-home care. Patients with risk factors, such as diabetes, were more likely to be transferred to healthcare facilities. For safe at-home care, it is necessary to prepare for an appropriate response to the emergency.